Gestión administrativa-financiera y su incidencia en la rentabilidad de la compañía Ventascorp S.A.de la ciudad de Quevedo, periodo 2011-2012, modelo de Gestión. - Espinoza Cercado, Jaime Gonzalo (2016)
Companies and organizations operate in an environment in which they are interrelated with their customers and suppliers, among others, and where they are not alone, because there are other companies that do the same, with which they compete. In this sense, all the companies in the same sector, industry or activity, make the industrial sector. The Quevedo’s city Ventascorp S.A Company, dedicated to the marketing of consumer products, does not escape having a number of strong competitors, in terms of lines marketing consumer products are concerned. It is vital to efficient administrative and financial management to achieve desired profitability by the shareholders of the company. That is why the big question highlights the research topic of this thesis: How administrative and financial management affects on the profitability of the Quevedo´s city Ventascorp S.A Company? This main objective thesis was to assess the incidence of administrative and financial management on the profitability of the Quevedo´s city Company Ventascorp S.A, in order to detect possible problems resulting from poor administrative and financial management and propose viable alternatives to improve it, if necessary. To reach the main objective of the research, it was necessary to identify administrative procedures and financial management, which is currently running the company. Furthermore, how human factor affects to achieve the objectives that the company pursues was investigated and, finally, analyzed the profitability of the Ventascorp SA Company, in order to optimize their revenues to benefit their shareholders and employes. Having done as described above, it was proceeded to raise the proposal, what consisting of a model of comprehensive administrative and financial management to strengthen the Ventascorp S.A, Quevedo´s city Company. This proposal will be of great socioeconomic impact.